Colaboração interprofissional entre docentes de ensino superior e profissionais de saúde da estratégia saúde da família em Juazeiro do Norte: estudo de caso. - Rocha, Francisca Alanny Araújo (2013)
This is a case study, qualitative approach, exploratory. The theoretical framework that guided the creation, design and the process of data collection, creation of research tools and further analysis of the data corpus paid field work was the concept of interprofessional collaboration and Typology of Interprofessional Collaboration D'AMOUR et al. (2008). The study took place in the town of Juazeiro where we investigated the collaborative process of managers and teachers from three private institutions that adopt the Family Health Strategy (FHS) as a field internship curriculum for their students, and managers and professional teams FHS. Data collection occurred during the month of August 2011 and in October 2012, having used the following techniques: field diary, open interview and review and analysis of documents with registration agreements and partnerships between the Municipal Health and HEIs. We analyzed each institution separately, discussing the process of interprofessional collaboration between teachers and health professionals, considering four dimensions: governance, shared goals and vision, formalization and internalisation, and ten indicators of the model reproduced schematically in chart Kiviat. To construct the graph of each IES, analyzed the interviewees' discourse, seeking to promote the mainstreaming of interviews of professionals from the municipal health system, which allowed visualization of the level of collaboration between organizations. The study was submitted to the Ethics Committee of the Universidade Estadual Vale do Acaraú (UVA), Protocol n ° 911. Thus, considering the question posed, the inferences regarding interprofessional collaboration between IES investigated and the ESF contribute incipient to the quality of undergraduate training and continuing education of professionals FHS has many weaknesses. The workspace of health facilities does not seem to be seen as a common ground for teachers, students and health professionals, and it probably results from a lack of leadership that lead the integration, aiming at strengthening practices qualified health community. Further research revealed the importance of inter-institutional and inter to promote activities such as health education, which end up being left in the background by the bureaucratization of work processes and the immediate demand that must be met in FHS units. It would be a fundamental approach of health literature that deals with the integration of teaching and service to bring clarity of what it means and what it proposes. Despite the limitations of the research, we did not assess, for example, the results of this process in vocational training, this can help to awaken in IES managers and health care systems and the need for closer ties to contribute to strengthening the quality of attention, promotion and continuing health education.